1989
DOI: 10.1177/0148607189013006663
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Cardiomyopathy Due to Selenium Deficiency

Abstract: Selenium is an essential trace element and a component of glutathione peroxidase, an enzyme that may help to prevent oxidative damage to cells. Selenium deficiency has been linked to the development of Keshan disease, a dilated congestive cardiomyopathy occurring primarily in children living in rural China. Sporadic cases have been reported in the United States in individuals with poor nutritional intake, mostly in individuals on long-term home parenteral nutrition. This report describes a young black woman wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 10 publications
1
30
0
Order By: Relevance
“…Dietary supplementation of 100 µg Se (sodium selenite) in patients submitted to total parenteral nutrition was shown to revert arrhythmias and cardiomegalies and lead to an increase in left ventricle ejection fraction (Saito et al 1998). In addition, the incidence of Keshan disease, an endemic dilated congestive myocardiopathy in areas of Se deficiency in China and Russia, has been shown to be prevented by oral Se supplementation at a dosage of 150-300 µg/week (Reeves et al 1989). It should be noted that Se supplementation has also been suggested as a strategy for prevention of myocardial diseases in other studies of human cardiopathy (Korpela et al 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary supplementation of 100 µg Se (sodium selenite) in patients submitted to total parenteral nutrition was shown to revert arrhythmias and cardiomegalies and lead to an increase in left ventricle ejection fraction (Saito et al 1998). In addition, the incidence of Keshan disease, an endemic dilated congestive myocardiopathy in areas of Se deficiency in China and Russia, has been shown to be prevented by oral Se supplementation at a dosage of 150-300 µg/week (Reeves et al 1989). It should be noted that Se supplementation has also been suggested as a strategy for prevention of myocardial diseases in other studies of human cardiopathy (Korpela et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Gomez et al (2002) have also reported an increased severity of myopathy in Se-depleted chronically infected mice; furthermore, Davis et al (1998) showed that Se supplementation reduced parasitaemia and mortality in infected mice. Based on these findings and taking into account the association of Se intake with the prevention of cardiac diseases (Korpela et al 1989, Reeves et al 1989, Foster & Sumar 1997, Saito et al 1998, we investigated the effect of Se treatment on the development of chronic cardiopathy in T. cruzi-infected mice in both prevention and reversion schemes.…”
mentioning
confidence: 99%
“…Obtained primarily from dietary sources, reductions in serum Zn and Se have been associated with the appearance of a dilated cardiomyopathy. [34][35][36][37] Of interest, urinary Zn excretion is increased in response to treatment with angiotensinconverting enzyme inhibitor or angiotensin receptor antagonist and where hypozincemia is held responsible for the appearance of disturbances of taste. [38][39][40][41] In recent studies conducted in Memphis in middle-aged African-American patients having a dilated cardiomyopathy of uncertain etiology, reductions in serum Zn and Se were found and included those patients hospitalized with decompensated failure and outpatients with compensated failure.…”
Section: Chf: a Salt-avid Statementioning
confidence: 99%
“…The results of a number of studies about cardiac disease induced by selenium deficiency, such as Keshan disease that has been controlled with oral replacement of sodium selenite, have been published [12][13][14] . Most of the studies reported patients who had undergone long-term parenteral nutrition without selenium replacement, or patients with acquired immunodeficiency syndrome and severe undernourishment [15][16][17] .…”
mentioning
confidence: 99%